STRENGTH OF INTERMEDIATE LENGTH TUBULAR STEEL COLUMNS – BARE, CONCRETE FILLED, RETROFITTED OR REHABILITATED - Narayanan, S.P; Kalaikumar, V.; Cossa , N.J; Hasifi, M.S. (2010)
Steel tubular members are used in high rise buildings, industrial structures, piles, bridge piers and offshore structures. The strength of short length steel tubular – bare or infilled with normal concrete – is widely reported. The codes provide expressions for evaluating the nominal strength of short and long, bare and infilled steel columns. Not many studies on intermediate length steel columns are reported. The ongoing research on concrete infilled steel tubular sections has the following aspects: (1) Steel tubulars of length 1200 mm infilled with concrete of grades 30, 60 and 80 N/mm2 tested in axial compression and comparison with the code predicted ultimate strengths using EC4, BS5400, ACI, AS and AIJ. The results show that BS5400 predicted values were 30% lower than experimental results whereas ACI, AS and AIJ predictions were 5% higher for concrete 60Mpa and 80 MPa. (2) Rehabilitation of artificially damaged tubulars using concrete, grout and CFRP sheets. The “artificial damage” simulating typical patch corrosion reduced the ultimate strength by 5-23%. Concrete filled tubulars when corroded had reduced strength by 40-50%. The several retrofit methods showed significant increase in strength. However, grout infill showed highest strength gain, followed by concrete infill. CFRP retrofit showed only limited increase.